PsycEXTRA Dataset 2006
DOI: 10.1037/e540562006-001
|View full text |Cite
|
Sign up to set email alerts
|

Enterovirus Surveillance - United States, 1970-2005

Abstract: depar depar depar depar department of health and human ser tment of health and human ser tment of health and human ser tment of health and human ser tment of health and human services vices vices vices vices

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

31
520
8
41

Year Published

2007
2007
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 439 publications
(626 citation statements)
references
References 112 publications
31
520
8
41
Order By: Relevance
“…Enteroviruses, members of the Picornaviridae family, are among the most common human-infecting viruses worldwide [1]. They are associated with several human diseases that cause a wide range of clinical syndromes, such as the common cold; hand, foot, and mouth disease (HFMD); acute flaccid paralysis; acute hemorrhagic conjunctivitis; aseptic meningitis; and myocarditis [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…Enteroviruses, members of the Picornaviridae family, are among the most common human-infecting viruses worldwide [1]. They are associated with several human diseases that cause a wide range of clinical syndromes, such as the common cold; hand, foot, and mouth disease (HFMD); acute flaccid paralysis; acute hemorrhagic conjunctivitis; aseptic meningitis; and myocarditis [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…Coxsackievirus B (CVB) 3 infection is commonly associated with myocarditis (2). Although myocarditis is increased in men, rates of infection with CVB are similar between men and women worldwide (3)(4)(5). The lower incidence of heart disease in women has been attributed to the cardioprotective effects of estrogen (6).…”
mentioning
confidence: 99%
“…As for viruses of the family Picornaviridae, viruses of different genera have different seasonal patterns of activity. For example, enteroviruses are more active during the summer months, whereas rhinoviruses usually have spring and autumn peaks (Khetsuriani et al, 2006;Monto, 2002). In this study, almost all TV1, TV2 and TV3 were found in November, December and January.…”
Section: P C Y Woo and Othersmentioning
confidence: 67%